BUILDING AWARENESS FOR A GREEN ECONOMY: AN ANALYSIS OF GEYO.IDN’S SOCIAL MEDIA STRATEGY USING THE FOUR PILLARS THEORY - Go, Priskila; Nurkhamidah, Neni; Nofiasari, Wida; Rahmat, Felisianus Novandri (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Environmental campaigns on social media often face challenges in sustaining engagement and driving behavioral change, as initial interest frequently wanes, limiting long-term impact. While social media effectively raises awareness, targeted strategies are essential for inspiring meaningful action. This study examines the social media strategies of the Green Economy Youth Organization (@geyo.idn), focusing on its ability to engage youth and promote sustainability through community initiatives and educational posts. Using a qualitative approach guided by the Miles and Huberman model, a case study method was employed to analyze @geyo.idn’s campaigns. Content analysis, framed by the Four Pillars of Social Media Strategy—Communication, Collaboration, Education, and Entertainment— proposed by Safko & Brake (2009), was applied to assess post language, visuals, and interactive features. Findings reveal that @geyo.idn predominantly employs Collaboration and Education strategies, reflecting audience preferences for meaningful and actionable content. High-engagement posts successfully combine multiple pillars, particularly where Collaboration and Communication dominate, with Education linking activities to broader sustainability goals and Entertainment enhancing overall appeal. This integration of pillars fosters audience participation and sustained awareness. The research concludes that while @geyo.idn effectively leverages Collaboration and Education to drive engagement, incorporating more Entertainment elements could diversify its approach and sustain long-term interaction. Future campaigns should continue emphasizing clear communication while exploring creative and interactive formats to broaden appeal and impact.